2001
DOI: 10.1186/1472-6947-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Computerized clinical documentation system in the pediatric intensive care unit

Abstract: BackgroundTo determine whether a computerized clinical documentation system (CDS): 1) decreased time spent charting and increased time spent in patient care; 2) decreased medication errors; 3) improved clinical decision making; 4) improved quality of documentation; and/or 5) improved shift to shift nursing continuity.MethodsBefore and after implementation of CDS, a time study involving nursing care, medication delivery, and normalization of serum calcium and potassium values was performed. In addition, an eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 6 publications
0
49
0
Order By: Relevance
“…Online parenteral nutrition calculator [23][24][25][26][27][28][29][30] IV administration technology (n = 4) Auomated infusion devices [19][20][21][22] Barcoding (n = 3) Barcode medication administration system [31][32][33] Organizational (n = 16) Guidelines, policies, and procedures (n = 9)…”
Section: Intervention Type Example Of Intervention Referencesmentioning
confidence: 99%
“…Online parenteral nutrition calculator [23][24][25][26][27][28][29][30] IV administration technology (n = 4) Auomated infusion devices [19][20][21][22] Barcoding (n = 3) Barcode medication administration system [31][32][33] Organizational (n = 16) Guidelines, policies, and procedures (n = 9)…”
Section: Intervention Type Example Of Intervention Referencesmentioning
confidence: 99%
“…These systems are based on populating forms and templates using data extracted from an electronic patient record -they do not use NLG technology to summarise the data in the patient record. Menke et al [10] found that the use of such a system in a paediatric ICU increased the quality and accuracy of documents; however they did not report any significant differences in error rates or patient outcomes. Strople and Ottani [11] made a good case for the desirability of using computers to at least partially automate the shift handover process, but did not describe or evaluate an actual system.…”
Section: Computerised Shift Handovermentioning
confidence: 99%
“…Up-to-date and accurate [12], [23] Fundamental problems such as lack of computer skills, complex tasks, complex functions [6]; [10]; [30] [37]; [47]; [48] Decrease medical errors [24]; [25], [26], [27]; [28]; [29]; [30]; [31]; [32]; [33]; [34]; [35]; [36] Ethical issues such as certification, security, privacy and confidentiality [26]; [41]; [48] …”
Section: A Hospital Information System (His)mentioning
confidence: 99%